AMANAH SEBAGAI KONSEP PENGENDALIAN INTERNAL PADA PELAPORAN KEUANGAN MASJID (Studi Kasus pada Masjid di Lingkungan Universitas Diponegoro) - Zoelisty, Capridiea; Adityawarman, Adityawarman (Diponegoro Journal of Accounting, 2014)
This study aims to analyze the trust manager of the mosque in managing funds associated with the financial reporting environment in particular mosque mosque in the University of Diponegoro, test and analyze managers to manage funds, especially in the area of Diponegoro University Mosque, test and analyze the application of internal controls that have been made manager mosque mosque in managing funds especially in the area of Diponegoro University, as well as to understand the application of internal control that has been done in the mosque authorities to manage the funds and determine barriers to the implementation of internal control and how to overcome these obstacles. This study used qualitative methods with case study approach. The results of this study show that the mandate is an attitude that is very important to the concept of internal control in this study.